The Mental Health of Male Sexual Minority Asylum Seekers and Refugees in Nairobi, Kenya: A Qualitative Assessment - Misedah-Robinson, Lourence; Schick, Vanessa; Ross, Michael W.; Wambua, Solomon (Refuge: Canada’s Journal on Refugees, 2022)
Very little information exists about the experiences of asylum seekers and refugees who are men who have sex with men (MSM). Therefore, this study explores the psychological distress of MSM asylum seekers and refugees in the Nairobi metropolitan area. We collected data using in-depth interviews transcribed verbatim, coded using NVivo 12 Plus, and analyzed using the six-step thematic analysis framework. Four major themes emerged from the study: psychological distress, traumatic stress symptoms, mental health care access, and coping strategies. Although we did not use any diagnoses, the results indicate that MSM asylum seekers and refugees share mental health problems with other refugees. However, MSM have specific needs that derive from their persecution based on their sexual minority status. The results confirm extant findings, as seen in the discussion, and encourage more research. Further research will inform collaborative, culturally sensitive, and targeted interventions that decrease adverse mental health outcomes for MSM asylum seekers and refugees in the Nairobi metropolitan area.